Synthesis, characterisation and synergistic effect of ZnO nanoparticles to antimicrobial activity of silver nanoparticle. (2021) - Sachdeva, Amit; Singh, Shruti; Singh, Pramod K.
Abstract: Silver and Zinc oxide nanoparticles has been synthesised using wet chemical method and characterized using various techniques like UV–Vis Spectroscopy, Scanning Electron Microscopy and X-Ray Diffraction studies. UV–Vis results depicted the characteristic SPR peak for silver as well as ZnO nanoparticles. SEM results helped in studying the surface morphology along with particle size. XRD patter narrated about crystallinity of the prepared samples along with confirming the particle dimensions. Both the nanoparticles were mixed in different concentrations and their antimicrobial properties were evaluated. It has been observed that at a particular concentration the composite showed maximum anti-microbial activity.